Islam dan Ekslusi Dalam Budaya Rantau Masyarakat Bawean Abad ke- 20 Sampai Awal Abad ke- 21 - Fasih, Ulum; Zamzani, Pratiwi Nur; Riantoro, Subandi (Prodi Ilmu Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Jambi, 2022)
This study of local history of the Bawean community analyzes the factors that shape the culture of exclusion of the Bawean people overseas. The research uses a literature-based historical method by starting with open-ended questions. Then interpret the existing literature such as preliminary scientific studies on Bawean and then draw interpretations to produce answers in the form of historiography of local history. This study concludes that the factors that shape the culture of exclusion of the Bawean people in their areas of origin to overseas are supported by various factors, such as local culture, educational inequality and unequal access to knowledge and life values. This conclusion is part of Bawean local history writing which combines local history writing with cultural history. Keywords: Bawean, Culture, Exclusion,